TERJEMAHAN SHUUJOSHI YO PADA SUBTITLE BAHASA INDONESIA DALAM SERIAL TELEVISI ANIMASI ORE, TSUSHIMA KARYA OPUUNOKYOUDAI - M. Syafri, M. Syafri; Aibonotika, Arza; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aims to describe the function of shuujoshi yo containedin the animated television series Ore, Tsushima. This research is a qualitativedescriptive research using descriptive methods and using library techniques and notetakingtechniques. The data source was taken from the animated television series Ore,Tsushima. The results of the research can be concluded that there are 22 shuujoshi yoin the form of dialogue and narrative sentences in the animated television series Ore,Tsushima. The function of shuujoshi yo is found to be 'conveying something that thelistener is not aware of or does not know', complementing the speaker's own uncertainknowledge with the listener's information', 'refuting the interlocutor's difference ofopinion with himself', and 'demanding sentences in which contains commands,prohibitions, requests and invitations'.Key words: Function, Shuujoshi yo, Translation